Biosugars production from napier grass used in phytoremediation of palm oil mill effluent final discharge - Osman, Nurul Atiqah (2020)
Napier grass is well known as a substrate for biosugars production, due to its considerable cellulose content. It also has suitable features as phytoremediator in treating wastewater, for example, high growth rate and high tolerance to contaminants. A study has proven that phytoremediation of palm oil mill effluent final discharge (POME FD) using Napier grass can be applied in constructed wetland treatment system. However, the potential of utilising Napier grass after phytoremediation of POME FD has not been fully studied. Therefore, it is crucial to study the properties of the Napier grass, which include the physical analysis, lignocellulosic composition, and elements and heavy metals concentration deposited in the plant after phytoremediation. Apart from that, the compounds in POME FD may influence cellulose content in plants, and can inhibit saccharification process. Therefore, it is important to determine the effect of POME FD on the yield of biosugars obtained after saccharification. In this study, the effect of POME FD on the Napier grass cultivars (Common and Red cultivar) in a constructed wetland system was evaluated. The two months old Napier grass cultivars were used in this study. The treatment systems were supplied with 5 litre of POME FD per day, whereas the control systems were supplied with rainwater at 5 litre every day, for 8 weeks. The height and the number of tiller and leaves, were measured for every weeks. The plants were harvested at week 8. The stems were pressed and the juice obtained were analysed for sugar and elements content determination. The dried stems and leaves were used for the lignocellulosic composition analysis, while only stem sample were used in the alkaline pretreatment and saccharification for biosugars determination. A 20 FPU/gsubstrate of Acremonium cellulase was used in the saccharification. The results revealed that the percentage of height increments of the plant from week 0 to week 8 in treatment system for Common and Red cultivars were 61.72 ± 2.36% and 109.98 ± 2.05%, respectively, as compared to those in control, which were 14.42 ± 2.11% and 30.30 ± 1.75%, respectively. These results indicated the ability of Napier grass to absorb the necessary nutrients from POME FD for plant growth. Besides, Napier grass cultivar grown in treatment system have higher cellulose percentage (38.77 ± 0.29% and 42.29 ± 0.95%, for Common and Red cultivar, respectively) compared with control (34.16 ± 1.01% and 36.14± 0.45%, respectively). Thus, it is more suitable as substrate for biosugars production. In addition, the result revealed that heavy metals concentration absorbed and accumulated in Napier grass stem, leaves and juice were below the standard limit of World Health Organization (WHO). As for glucose conversion yield percentage, there is no significant difference between the treatment and control biomass. This suggested that concentration of elements deposited in stem of treatment system biomass does not inhibit saccharification process. The findings of this study can be used as a reference for further utilisation of Napier grass after being used in the phytoremediation of POME FD.